Ejecutabilidad del silencio administrativo en el Ecuador y su incidencia en el administrado - Robalino Andino, Sandra Verónica (2022)
ABSTRACT: The present investigation addresses the problems generated by the execution of Administrative Silence, as well as the implications derived from the legal practice of this principle. As the main objective of the study, an analysis of the enforceability of Administrative Silence was carried out through the current legal doctrinal practice in Ecuador to determine the incidence in the administered, for which it was necessary to identify the current regulations, establish the cases of applicability of the Administrative silence and determine the practice of this same principle. For this analysis, a methodology with a qualitative approach, of a documentary and descriptive bibliographic nature, was applied. Among the results obtained, it was determined that the causes to apply the Administrative Silence are the omissions of the entity, however, the requests usually incur uncontainable defects that lead to declaring the unenforceability of the requests made by the administered. Finally, it was concluded that even though the regulations that govern Administrative Silence in the country generate conditions for the enforceability of this principle, in judicial practice the opinion for this type of process generally establishes unenforceability due to the grounds for nullity established. in the law generating a degree of incidence on the administered. Keywords: Administrative Silence, Managed, Administration, Administrative Law, Right of Petition.